Utilisation of interpretive structural modelling method in the analysis of interrelationship of vendor performance factors. (1st January 2011) - Lin, Ya-Ti; Lin, Chia-Li; Yu, Hsiao-Cheng; Tzeng, Gwo-Hshiung
Vendor performance is a crucial factor affecting the success of outsourcing operations today. It is essential to understand the interrelationship in a complex performance analysis framework, for it helps to identify the root causes that affect other criteria as well as the overall performance. The purpose and contribution of this paper is to propose the use of interpretive structural modelling (ISM) method to provide an understanding of the causal interrelationship in the complex vendor performance evaluation framework, and in return, enables the firms to make analysis and improvements more accurately and efficient. A case study is conducted to analyse the causal interrelationship of a wafer-testing vendor's performance in Taiwan's semiconductor industry to present the proposed procedure. The proposed ISM method of this research is not only useful for distinguishing the causal interrelationship in a complex problem but also able to be extended to support other quantitative multiple-criteria decision-making methods in obtaining the weights of each evaluation criterion.